Evaluating Brivaracetam As An Adjunctive Therapy For Refractory Focal Onset Seizure: A Meta-Analysis - Chandra Kusuma, Hendrawan; Isadora, Eugenia; Putra, Aditya; Kurniawan Sindaka, Jonathan (Departemen Neurologi Fakultas Kedokteran Universitas Indonesia, 2025)
Background: This study evaluated the safety, tolerability and effectiveness of Brivaracetam (BRV) as an adjunctive therapy for managing focal-onset seizures that are uncontrolled by primary antiseizure medications (ASMs). Method: This review systematically incorporated studies from databases including PubMed, ProQuest, The Lancet, EBSCO and the Cochrane Library. Study quality was assessed using the Cochrane Risk of Bias 2 tool. Meta-analysis was conducted with Review Manager 5.4. Result: Seven studies were included, with five qualifying for meta-analysis involving 2,486 patients taking BRV alongside one or more AEDs. The pooled risk ratios for a 50% reduction in seizure frequency and complete seizure freedom were 1.83 (95% confidence interval of 1.60 to 2.08) and 7.52 (95% confidence interval of 3.59 to 15.75), respectively. In terms of safety, the use of adjunctive BRV was linked to significantly higher rates of somnolence (p<0.00001), dizziness (p=0.0001), and fatigue (p=0.0002), along with other drug-related treatment-emergent adverse effects (TEAEs) such as headache, irritability and nausea. There was no significant difference (p>0.05) between the two groups regarding serious adverse effects (SAEs) or the number of patients who withdrew from the study due to drug-related TEAEs or SAEs. Discussion: Adjunctive BRV (50-200 mg daily) notably enhanced efficacy outcomes compared to placebo. While mild to moderate side effects occurred, there were no significant differences in SAEs and withdrawal rate, indicating a favorable safety and tolerability profile that aligns with other adjunctive ASMs. Conclusion: BRV (50–200 mg) is favourable adjunctive therapy for uncontrolled focal-onset seizures.